2016
DOI: 10.1111/ggi.12932
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Chronic Kidney Disease Epidemiological Collaboration and Berlin Initiative Study equations for estimating glomerular filtration rate in older people: The Invecchiare in Chianti (Aging in Chianti Region) study

Abstract: Aim The aim was to investigate to what extent chronic kidney disease (CKD) can be staged interchangeably by Chronic Kidney Disease Epidemiological Collaboration (CKD-EPI) and by Berlin Initiative Study (BIS) equations, and to verify whether cystatin C can improve concordance between formulas. Methods Our series consisted of 828 community-dwelling individuals aged 65 years or older enrolled in the Invecchiare in Chianti Study (“Aging in the Chianti Region”). Estimated glomerular filtration rate was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
5
10
1
Order By: Relevance
“…The diagnosis of these CKD stages is very important for determining the specific diagnostic and therapeutic measures to be recommended. [ 9 ] These findings were similar to those of a previous study reported by Corsonello et al [ 10 ] involving elderly individuals approximately 80 years old. The CKD-EPI equation classified more patients with CKD stage 5 than the BIS1 equation.…”
Section: Discussionsupporting
confidence: 91%
“…The diagnosis of these CKD stages is very important for determining the specific diagnostic and therapeutic measures to be recommended. [ 9 ] These findings were similar to those of a previous study reported by Corsonello et al [ 10 ] involving elderly individuals approximately 80 years old. The CKD-EPI equation classified more patients with CKD stage 5 than the BIS1 equation.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies reported on discrepancies between eGFR values obtained with different equations, but only a few of them included the most recently published BIS and FAS equations at the same time. A former study showed that the average difference between creatinine-based CKD-EPI and BIS was 9.5 mL/min/1.73 m 2 in a population of 828 community-dwelling older people [16], which is very close to the 8.97 mL/min/1.73 m 2 difference observed in the present study. The average 8.72 mL/min/1.73 m 2 difference between CKD-EPI and FAS, as well as the negligible average difference between BIS and FAS are not surprising given the fact that FAS has been designed to match the BIS equation for ages >70 years [11].…”
Section: Discussionsupporting
confidence: 89%
“…Other biomarkers of kidney function, especially cystatin C, were investigated in an attempt to improve the accuracy of kidney function estimates. While the accuracy of equations including both creatinine and cystatin C in predicting measured GFR was found to be better than that observed with creatinine-based ones among older patients [15], the agreement between equations was found to be only marginally improved [16] and prognostic accuracy unchanged when adding cystatin C [17]. Thus, the additional costs generated by cystatin C assessment may not be associated with a true improvement in clinical assessment of kidney function.…”
Section: Introductionmentioning
confidence: 83%
“…In groups stratified by sex ( Fig. 4), differences in these three equations were higher in female participants than in male participants, consistent with the findings of a previous study (Corsonello et al, 2017). Notably, the eGFR tended to be overestimated when these three equations were used in women.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, the selection of older adults for diagnostic and therapeutic interventions related to CKD stage changes depends on which equation is used (Changjie et al, 2017). Thus, considering the discordance among these equations with regard to their respective accuracies for predicting measured GFR has practical clinical implications (Corsonello et al, 2017). Centenarians represent a unique population in experimental research because they develop all the signs and characteristics of the extreme aging process (Puca et al, 2017).…”
Section: Introductionmentioning
confidence: 99%